Personal Branding Influencer @Angelillc melalui TikTok - Angelica, Silvia Alverina; Loisa, Riris (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
This research was conducted using a descriptive qualitative approach. Researchers conducted in-depth interviews and observations of one of the beauty & fashion influencers in Indonesia, namely Angelillc as a research subject. Interviews were conducted via online and voice recording. The purpose of this study is that researchers can find out the process of forming personal branding that occurs at Angelillc through the social media TikTok so that the public knows the characteristics that exist in an Angelillc. The results of this study are to find out the process of forming Angelillc's personal branding which was accidentally formed by editing content and mix & match clothes from e-commerce whose prices are fairly cheap but of high quality. In addition, Angelillc always creates content that is relevant to the needs of the public and always communicates with its followers. So that Angelillc's personal branding is increasingly recognized. Angelillc can also provide cheap beauty product recommendations by directly providing direct reviews in the content via social media TikTok. TikTok adalah media sosial yang banyak digunakan influencer untuk melakukan personal branding. Tak hanyak itu, media ini pun digunakan untuk memasarkan produk serta dan juga sebagai medium komunikasi dengan pelanggan. Begitu juga dengan Angelillc satu beauty & fashion influencer di Indonesia. Penelitian ini dilakukan dengan menggunakan pendekatan kualitatif yang bersifat deskriptif. Tujuan dari penelitian ini adalah peneliti dapat mengetahui proses pembentukan personal branding yang terjadi pada Angelillc melalui media sosial TikTok sehingga publik mengetahui ke ciri khas an yang ada pada seorang Angelillc. Hasil dari penelitian ini adalah mengetahui proses pembentukan personal branding Angelillc yang secara tidak sengaja terbentuk dengan melakukan editing konten dan mix & match baju dari e-commerce yang harganya terbilang sangat murah tetapi berkualitas. Selain itu Angelillc selalu membuat konten yang relevan dengan kebutuhan publik dan selalu berkomunikasi dengan pengikutnya. Sehingga personal branding Angelillc semakin dikenal. Angelillc juga dapat memberikan rekomendasi produk kecantikan yang murah dengan langsung memberikan review langsung di dalam konten melalui media sosial TikTok.